2020
DOI: 10.15252/embj.2019103841
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation switches protein disulfide isomerase activity to maintain proteostasis and attenuate ER stress

Abstract: Accumulated unfolded proteins in the endoplasmic reticulum (ER) trigger the unfolded protein response (UPR) to increase ER protein folding capacity. ER proteostasis and UPR signaling need to be regulated in a precise and timely manner. Here, we identify phosphorylation of protein disulfide isomerase (PDI), one of the most abundant and critical folding catalysts in the ER, as an early event during ER stress. The secretory pathway kinase Fam20C phosphorylates Ser357 of PDI and responds rapidly to various ER stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 71 publications
0
77
0
Order By: Relevance
“…PDI is a multifunctional protein catalyzes the formation, breakage and rearrangement of disulfide bonds [83] or functions as a chaperone at high concentrations [84]. Recently, S357 of PDI was found to be phosphorylated by Fam20C and induce an open conformation of PDI that can bind to the lumenal domain of IRE1α and attenuate excessive IRE1α activity [85].…”
Section: Negative Feedback Loop In the Er Stress Responsementioning
confidence: 99%
“…PDI is a multifunctional protein catalyzes the formation, breakage and rearrangement of disulfide bonds [83] or functions as a chaperone at high concentrations [84]. Recently, S357 of PDI was found to be phosphorylated by Fam20C and induce an open conformation of PDI that can bind to the lumenal domain of IRE1α and attenuate excessive IRE1α activity [85].…”
Section: Negative Feedback Loop In the Er Stress Responsementioning
confidence: 99%
“…The prototype member of the family PDIA1 is localized primarily in the endoplasmic reticulum but nuclear, mitochondrial and localization on the surface of the cellular membrane has also been reported ( 43 ). PDIA1 exerts tumor-stimulating or suppressing effects being involved in a wide spectrum of physiological functions in a manner dependent on the type of tissue, microenvironmental conditions, subcellular localization and its oxidized or reduced conformation ( 10 12 ). To shed light on the role of the PDIA1 in breast carcinogenesis we followed a variety of ROS modulated pathways in the estrogen receptor positive MCF-7 and the ERα negative MDA-MB-231 cells under differential oxidative stress conditions in the presence or absence of PDIA1.…”
Section: Discussionmentioning
confidence: 99%
“…PDIA1 has been shown to modulate cellular oxidative stress mediating homeostasis of the antioxidant glutathione ( 8 ) and its function is regulated by cellular redox state. Specifically, PDIA1 exerts chaperone and isomerase activities in an oxidative stress-dependent manner facilitating redox-mediated regulation of protein folding ( 9 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported that PDI is specifically phosphorylated by the secretory pathway kinase Fam20C during ER stress. [ 84 ] Fam20C, the bona fide kinase for a majority of the secreted phosphoproteome, [ 85,86 ] was found to also phosphorylate and regulate Ero1α, the oxidase of PDI. [ 87 ] By mass spectrum analysis and a site‐specific antibody, we demonstrated that Ser357, located in the x ‐linker region, is a major Fam20C‐dependent phosphosite in PDI.…”
Section: Multiple Regulatory Modes Of Pdimentioning
confidence: 99%